PENGARUH EKUITAS MEREK DAN PREFERENSI MEREK TERHADAP KEINGINAN MEMBELI KEMBALI HP NOKIA ( Studi Pada Konsumen HP Nokia di Kota Semarang ) - Jefri Handiarko, 08.05.51.0061; Maskur, Ali (Students Journal of Economic and Management, 2013)
Brand is a name, term, sign, symbol design, or combination thereof that identifies a product / service is thetangible and intangible values that are represented in a trademark (trademark) that is able to create value and its owninfluence on the market when it is set correctly.According to David A. Aaker (1991) the basic concept of brand equity (brand equity) can be grouped into 5elements of brand loyalty (brand loyalty) brand awareness (brand awareness) impression of the quality (perceived quality)brand association (brand association) the assets of the rights of other brands (other proprietary brand assets).Brand preferences created from a set of attributes that have been known and in a relatively higher value bykonsumen.Dengan strong preference, then the probability of consumers will buy a particular companys products comparedto competitors is certainly higher. Researchers Allison (1964) showed that the most famous member of a higher preferencefor familiar brands than at the time the test is performed with a blind taste test.In conducting this study, respondents to be studied is the consumer in Semarang city that never make a decisionto purchase the Nokia brand mobile products, and the study was conducted in the city of Semarang as the study populationbecause consumers in Semarang is a segment of society that makes information and communication as a daily needs,because that phone is needed by everyone to communicate and exchange information needed to umumnya.Dengan is theconsumer needs in the city of Semarang is one customer with a level of equitable purchase mobile products, especiallymobile phone brand Nokia is created for all segments of the community in accordance with the motto "Connecting PeopleâKeywords: brand equity, brand preference and desire to buy back